Trends in atmospheric HFC-23 (CHF3) and HFC-134a abundances. (November 2019) - Fernando, Anton M.; Bernath, Peter F.; Boone, Christopher D.
Highlights: Linear trends of atmospheric HFC-134a and CHF3 from ACE-FTS data. Description of HFC-134a and CHF3 retrievals. Comparison with Advanced Global Atmospheric Gases Experiment (AGAGE) data. Abstract: The Montreal Protocol banned the production of major ozone depleting substances such as chlorofluorocarbons (CFCs) to protect the Earth's ozone layer. The resulting increased production and emissions of CFC-replacement hydrofluorocarbons (HFCs) has caused a dramatic increase in their atmospheric abundances. Although these HFCs do not contribute directly to the depletion of the ozone layer because they contain no chlorine, they are powerful greenhouse gases with large global warming potentials. In January 2019, the Kigali Amendment to the Montreal Protocol came into force to phase out long-lived HFCs. The two most abundant HFCs in the atmosphere, HFC-134a (CF3 CH2 F) and HFC-23 (CHF3 ), are measured from orbit by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS). These measurements will be useful for monitoring the Kigali Amendment to the Montreal Protocol. Analysis of the ACE-FTS measurements provides near-global distributions and confirms the rapid increase in HFC-134a (4.9 ± 0.1 ppt per year) and HFC-23 (0.75 ± 0.02 ppt per year) volume mixing ratios (VMRs).